Safety and Efficacy of Newer Oral Anticoagulants in Coronary Artery Disease Patients: A Prospective Observational Study - Kandukuri , Murali Krishna; Karthickeyan, K. (Journal of Neonatal Surgery, 2025)
Background: Coronary artery disease (CAD) is a major contributor to morbidity and mortality globally. Anticoagulation plays a pivotal role in managing thromboembolic complications. While traditional anticoagulants like warfarin and heparin are widely used, they are associated with limitations including bleeding risks and intensive monitoring. Newer oral anticoagulants (NOACs) such as apixaban and dabigatran offer a promising alternative. Objective: To prospectively evaluate and compare the safety and adverse effect profile of newer oral anticoagulants (apixaban, dabigatran) with traditional agents (warfarin, heparin) in CAD patients under real-world clinical conditions. Methods: A 12-month, open-label, parallel-group, observational study was conducted at Vijaya Hospital, Nellore. A total of 200 patients aged 30–60 with diagnosed CAD were included—100 on NOACs and 100 on older agents. Adverse drug reactions (ADRs) were evaluated using a structured questionnaire (CADSEQ), patient diaries, and WHO-UMC causality assessment. Results: NOACs exhibited significantly fewer adverse events (13%) compared to warfarin/heparin (42%). Major bleeding, liver dysfunction, and hypersensitivity reactions were markedly lower in the NOAC group (p< 0.05). Patient adherence and satisfaction were improved with NOACs due to ease of administration and reduced monitoring needs. Conclusion: NOACs demonstrate superior safety, tolerability, and compliance in CAD management. Their role should be expanded, especially in high-risk or poorly monitored populations. Further studies in special populations such as neonates or pediatric CAD cases may help shape safe usage protocols.